Desain Kurikulum Sekolah Minggu Menggunakan Subject-Centered Design - Manalu, Debora; Purba, Berliana (Sekolah Tinggi Teologi Berita Hidup, 2023)
Good teaching on Sunday School will have an impact in the future for the growth and development of the church. The teaching is given by a Sunday School teacher centered on the Word of God. By teaching God's Word to Sunday School children, they have carried out the great commission of the Lord Jesus in Mark 10:14 and Matthew 28:19-3. However, the Word that is taught must first look at the context or condition of the Sunday School child so that the Word is processed, accepted and actualized by the child in daily life. For this reason, teachers need a method in developing and delivering God's Word in the church. The method that can be used by teachers is to use the curriculum. The curriculum suggested by the author for teaching is to use the Subject Centered Design curriculum which is centered on teaching materials or the Bible. The purpose of this research is to make it easier for Sunday school children to understand the contents of the Bible, to make it easier for Sunday school children to remember the contents of the Bible, to develop teaching patterns for Sunday school teachers in compiling learning materials sourced from the Bible, to find out teaching patterns using the Subject Centered Design curriculum. Thus, the Subject Centered Design curriculum is not only used in formal education, but the curriculum also applies in churches to foster Sunday School Children.Pengajaran yang baik terhadap Sekolah Minggu akan memberikan dampak ke depannya bagi pertumbuhan dan perkembangan gereja. Pengajaran tersebut diberikan oleh guru Sekolah Minggu yang berpusat pada Firman Tuhan. Dengan memberikan pengajaran Firman Tuhan kepada anak Sekolah Minggu sudah menjalankan amanat agung Tuhan Yesus dalam Markus 10:14 dan Matius 28:19-3. Namun Firman yang diajarkan harus melihat terlebih dahulu konteks atau kondisi anak Sekolah Minggu sehingga Firman itu diproses, diterima dan diaktualisasikan si anak dalam kehidupan sehari-hari. Untuk itu pengajar membutuhkan suatu metode dalam pengembangan dan penyampaian Firman Tuhan di gereja. Metode yang dapat digunakan pengajar adalah dengan menggunakan kurikulum. Kurikulum yang disarankan oleh penulis untuk melakukan pengajaran yaitu menggunakan kurikulum Subject Centered Design yang berpusat pada bahan ajar atau Alkitab. Adapun tujuan penelitian ini adalah untuk mempermudah anak Sekolah Minggu memahami isi Alkitab, untuk mempermudah anak Sekolah Minggu mengingat isi Alkitab, untuk mengembangkan pola pengajaran guru Sekolah Minggu dalam menyusun bahan pembelajaran yang bersumber dari Alkitab, untuk mengetahui pola pengajaran menggunakan kurikulum Subject Centered Design. Dengan demikian kurikulum Subject Centered Design tidak hanya digunakan dalam pendidikan formal namun kurikulum juga berlaku di gereja untuk membina Anak Sekolah Minggu.